Toxoplasma gondii virulence in mice is determined by the pseudokinase ROP5B and countered by an IRG-GBP protein interplay - Singh, Shishir; Murillo-León, Mateo; Bastidas Quintero, Aura María; Melbert, Florence; Pfeffer, Klaus; Degrandi, Daniel; Steinfeldt, Tobias (Frontiers in Immunology, 2025)
Toxoplasma gondii (T. gondii) virulence in mice depends on different multiprotein complexes that assemble at the parasitophorous vacuole membrane (PVM) of the parasite. Individual rhoptry proteins within these complexes inhibit different Immunity-Related GTPases (IRG proteins). The rhoptry pseudokinase ROP5 is a central element to achieve IRG-specific rhoptry kinase activity and/or efficient complex formation. The rop5 locus of each of the canonical T. gondii strains encodes three major isoforms, ROP5A, ROP5B and ROP5C, and was shown to have the largest impact on virulence. By reverse genetics, we have generated T. gondii strains expressing either ROP5A, ROP5B or ROP5C in a RHΔrop5 genetic background and demonstrate that ROP5B is mainly responsible for heightened virulence of type I T. gondii in laboratory strains of mice. In vivo virulence correlates with diminished vacuolar IRG protein loading and parasite control in vitro only in presence of ROP5B but not ROP5A or ROP5C. Our results suggest that ROP5A and ROP5C isoforms might have co-evolved with IRG proteins or other host cell resistance factors in evolutionarily important intermediate hosts beyond Mus musculus. The same parasite effectors that inhibit IRG protein accumulation and function reduce the vacuolar amount of Guanylate Binding Proteins (GBP proteins). However, a parasite effector targeting a GBP protein at the PVM has not been described yet. Using two different approaches, Yeast Two-Hybrid analysis and Protein-fragment complementation assay, we here identified three heterologous IRG:GBP pairs, GBP6:Irgb10, GBP5:Irgb10, GBP5:Irgb6, and demonstrate that the accumulation of these GTPases at the PVM is interdependent. Our results offer a novel perspective on the IRG and GBP protein-mediated control of T. gondii infections and may further advance the investigation of GBP-specific T. gondii effectors.